2018
DOI: 10.1520/mpc20170080
|View full text |Cite
|
Sign up to set email alerts
|

Review of Residual Stress Measurement by Magnetic Barkhausen Noise Technique

Abstract: Determination of residual stress state is important for quality, integrity, and service performance of the components and structures. Almost all manufacturing processes cause considerable amounts of residual stress; thus, any process or product design ignoring it involves a risk for distortion or early failure. Among the existing methods, the magnetic Barkhausen noise method has been gaining attention for measuring residual stresses nondestructively in ferromagnetic materials. It is sensitive to the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The BNM is a non-destructive method applicable to ferromagnetic materials that can be magnetized. It is based on magneto-elastic interaction, where the elastic properties vary with the domain and magnetic property of the specimen [56]. Barkhausen noise, defined as the variation in electrical pulses induced in a coil due to a jump in the magnetic force field of the specimen when small-order magnetic domains are aligned parallel to the applied magnetic field, is analyzed for RS characterization [45].…”
Section: Barkhausen Noise Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BNM is a non-destructive method applicable to ferromagnetic materials that can be magnetized. It is based on magneto-elastic interaction, where the elastic properties vary with the domain and magnetic property of the specimen [56]. Barkhausen noise, defined as the variation in electrical pulses induced in a coil due to a jump in the magnetic force field of the specimen when small-order magnetic domains are aligned parallel to the applied magnetic field, is analyzed for RS characterization [45].…”
Section: Barkhausen Noise Methodsmentioning
confidence: 99%
“…BNM is also influenced by the microstructure of the specimen. Hence, initial calibration is highly significant in obtaining accurate results using this method [56]. This feature limits the the application of the BNM for AM parts, as the microstructure is highly non-homogeneous.…”
Section: Barkhausen Noise Methodsmentioning
confidence: 99%
“…Javadi (2013) measured residual stress in stainless steel pipes due to welding using ultrasonic measurements and it was found that the residual stress around the weld centerline can be as high as 150 MPa (21.7 ksi), which was around 88% of its yield strength (170 MPa or 24.6 ksi). The X-ray diffraction method and MBN method were also applied to investigate the residual stress in welded structures and it was concluded that tensile residual stresses were generated at the welds due to the thermal contraction of the weld steel and the adjacent heated parent material during cooling after welding and that these tensile residual stresses can reach as high as the yield strength of the weld steel or the parent material (Fitzpatrick et al, 2005; Gur, 2018; Lachmann et al, 2000; Leggatt, 2008; Matzkanin and Gardner, 1976). Banahan (2008) investigated the structural integrity of a nuclear power-generating plant by including residual stress in his analysis.…”
Section: Significance Of Identifying Existing Stress For An Accurate mentioning
confidence: 99%
“…The micromagnetic, multiparameter, microstructure and stress analysis (3MA technology) can also be used for testing the stress-strain state [6]. Gur [7] and Gauthier et al [8] provide an overview of the application of the Barkhausen noise method to control mechanical stresses. The magnetic Barkhausen noise (MBN) method continues to be actively developed and used for the mechanical stresses testing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%